Barium Ferrite Magnet As Anti-Radar Material - Mohamad Ikhsan Nurulloh; Luhut Simbolon; George Royke Deksino (Universitas Muhammadiyah Purwokerto, 2022)
This article discusses barium ferrite magnets and their potential use as anti-radar materials for stealth technology in Indonesia. This study uses a variety of literature and the latest research results. Stealth technology was developed by creating an anti-radar substance capable of absorbing radar signals known as radar absorbing material. According to the literature review findings, barium ferrite-based magnets have the potential to be raw materials for radar wave absorbers since they absorb microwaves, including the frequency of waves utilized in radar. The magnetic characteristics and ability of barium ferrite magnets to absorb radar waves are affected by various conditions, including chemical and organic components. Barium ferrite magnets have been used as anti-radar materials in the military, in ships, aircraft, land vehicles, and clothing. The potential of barium ferrite as a determinant for modern military technology in Indonesia is considerable, but it is still limited in laboratory research. The Indonesian government can acquire stealth technology by implementing a dual-use technology strategy and a triple helix innovation model.